Inclination of Politics Among Dental Students - V, HEMANTH RAGAV N; GANAPATHY, DHANRAJ; SASANKA, KEERTHI (The journal of contemporary issues in business and government, 2020)
Politics is so much required as it offers students a platform to develop their leadership skills. The absence of politics in college campuses threatens to make them authoritarian and undemocratic, which is not good. It was an agreed statement that political parties have already destroyed our country and now are bent upon misguiding our youths with financial and judiciary powers. Student politics is generally viewed by those in authority as a negative factor, something to be eliminated from Academic life. Student politics sometimes affects higher education and on occasions sweeps beyond the campus to have disruptive implications for the political system. The Cross sectional study was done on dental students in tamilnadu. A well structured. Questionnaires on basis of inclination of politics among dental students were taken into consideration. This is an online based survey study and taken in english language.The sampling method used was a simple random sampling method. 10 Questionnaires were prepared and were administered through Google forms. In this study, 100 dental students were given the questionnaire and then the data was analysed. Mostly(85%) first year students responded to our survey. 64% of students responded that they like politics and the remaining 39% responded that they don’t like politics. According to the above survey we conclude that the attitude of the students shows a positive response of interest towards politics among the Dental students.